Struktur Kepemilikan, Karakteristik Dewan dan Biaya Keagenan: Analisis Hubungan Simultan - Evlin Handayani; Elok Pakaryaningsih (Fakultas Bisnis UKDW, 2008)
The obiective of this research is to examine the interdependent relationship between agency cost and board characteristics.. ising two ways i measurement, namely, ratios of OPEX and ATO, agency cost is hypothesized to have a simultaneous relationship with board characteristics miasured by board size and the proportion of outside directors. Farthermore, the variabieof corporate ownership measured by managerial ownership and blockholder ownership is used to examine its ffict on both agency cost and board characteristics. (Ising manufacturing industry listed at Jakarta Stock Exchange as the sample, the result shows the interdependent relationship issupported as well as the effect of corporate ownership on agency cost and board characteristics. Moreover the result also shows that agency cost measured by OPEX, robustly explain the interdependent relationship compare to ATO.Keywords: Corporate ownership, agency cost, board characteristics